Molecular Mechanisms of Plant Trichome Development - Han, Guoliang; Li, Yuxia; Yang, Zongran; Wang, Chengfeng; Zhang, Yuanyuan; Wang, Baoshan (Frontiers in Plant Science, 2022)
Plant trichomes, protrusions formed from specialized aboveground epidermal cells, provide protection against various biotic and abiotic stresses. Trichomes can be unicellular, bicellular or multicellular, with multiple branches or no branches at all. Unicellular trichomes are generally not secretory, whereas multicellular trichomes include both secretory and non-secretory hairs. The secretory trichomes release secondary metabolites such as artemisinin, which is valuable as an antimalarial agent. Cotton trichomes, also known as cotton fibers, are an important natural product for the textile industry. In recent years, much progress has been made in unraveling the molecular mechanisms of trichome formation in Arabidopsis thaliana, Gossypium hirsutum, Oryza sativa, Cucumis sativus, Solanum lycopersicum, Nicotiana tabacum, and Artemisia annua. Here, we review current knowledge of the molecular mechanisms underlying fate determination and initiation, elongation, and maturation of unicellular, bicellular and multicellular trichomes in several representative plants. We emphasize the regulatory roles of plant hormones, transcription factors, the cell cycle and epigenetic modifications in different stages of trichome development. Finally, we identify the obstacles and key points for future research on plant trichome development, and speculated the development relationship between the salt glands of halophytes and the trichomes of non-halophytes, which provides a reference for future studying the development of plant epidermal cells.